Sožitje staršev, otrok, medicinskih sester in zdravstvenih tehnikov v času zdravljenja otrok v bolnišnici - Kranjec, Tatjana (Obzornik zdravstvene nege, 2003)
Authors analyze the parent-child-nursing staff relationship on the pediatric surgical ward. The views of parents and nursing staff differ significantly on two issues. Firstly, on the perception of free parental access to the child and secondly, on how unrestricted visiting time influences the progress of child's recovery. Authors also asses how parents view the work of nursing staff and how nursing staff feels about parental involvement in the child's care. Parent's help in the process of care increases time the nursing staff has for other tasks.
Keywords: ankete; Child; Child, Hospitalized; health care; hospitalizacija; Medicinska sestra-bolnik, odnosi; Nurse-Patient Relations; Nursing Care; otroci; Otrok; Otrok hospitalizirani; Parents; Questionnaires; Starši; therapy; zdravljenje; Zdravstvena nega; zdravstvo